2018
DOI: 10.1080/09593330.2018.1435736
|View full text |Cite
|
Sign up to set email alerts
|

Use of Moringa oleifera seed extracts to polish effluents from natural systems treating faecal sludge

Abstract: The removal of pathogens in irrigation water is of great importance in developing countries. Indeed, wastewater generally reused for agriculture in countries such as Cameroon is associated with health and environmental concerns. Recent studies have shown a strong disinfectant action of the natural coagulant from the seeds of Moringa oleifera. These findings have raised the question whether or not they can be used to polish effluents from natural systems treating faecal sludge. This paper deals with trials carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…15). This decrease in bacteria counts was statistically significant (p=0.0003 at α=0.05), attributed to the antibacterial effect of MO introduced to FS, retaining the dead bacteria in the solid composition (Ngandjui et al, 2019). Silva et al (2013) further corroborated these findings, highlighting the strong disinfectant properties of the coagulant derived from the seed of M. Oleifera.…”
Section: Bacterial Removal Due To the Effect Of Moringa Oleifera (Mo)mentioning
confidence: 84%
“…15). This decrease in bacteria counts was statistically significant (p=0.0003 at α=0.05), attributed to the antibacterial effect of MO introduced to FS, retaining the dead bacteria in the solid composition (Ngandjui et al, 2019). Silva et al (2013) further corroborated these findings, highlighting the strong disinfectant properties of the coagulant derived from the seed of M. Oleifera.…”
Section: Bacterial Removal Due To the Effect Of Moringa Oleifera (Mo)mentioning
confidence: 84%
“…Indeed, moringa was used in the treatment of sewage sludges, wastewater, effluents, and different types of industrial wastes [ 111 , 137 , 215 , 219 , 229 , 246 , 311 , 391 ]. Studies in this respect, exploiting the potential of M. oleifera seeds as coagulants/flocculants, were carried out in Algeria [ 109 , 111 ], Kenya [ 229 ], Tunisia [ 391 ], Cameroon [ 137 , 140 ], Ghana [ 201 , 215 , 220 ], and Malawi [ 246 ]. Kilingo et al [ 229 ] pointed out that the use of moringa is “ a low-cost sewage treatment technology suitable for poor areas ” (p. 36589).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Cameroon showed that using 333 mg/L Moringa oleifera seed extracts as a coagulant in a vertical flow constructed wetland for the treatment of raw fecal sludge was insufficient in reducing Escherichia coli (86.74%), fecal coliforms (86.39%), and fecal streptococci (81.33%), and the effluent did not meet the Cameroon and World Health Organization (WHO) guidelines for safe wastewater reuse in agriculture and concluded that more studies are needed (Tchangoue et al, 2019).…”
Section: Safetymentioning
confidence: 99%